Comprehensive mitochondrial genomics of Fasciola gigantica from Sudan: insights into genetic diversity, evolutionary dynamics, and host adaptation - Salim, Bashir; Mohamed, Nouh S.; Ibrahim, Kamal; Alasmari, Saeed; Chatanga, Elisha; Ohari, Yuma; Nonaka, Nariaki; Alsaad, Mohammad A.; Almathen, Faisal; Nakao, Ryo (Frontiers in Veterinary Science, 2025)
IntroductionThis study presents a comprehensive analysis of the complete mitochondrial genomes of Fasciola gigantica isolated from cattle, sheep, and goats in Sudan, aiming to provide new insights into genetic diversity, evolutionary dynamics, and host adaptation.MethodsMitochondrial genomes were sequenced using high-throughput Illumina MiSeq technology, yielding sequences of 14,483 bp, slightly longer than the reference genome (14,478 bp). A sliding window analysis was conducted to assess nucleotide diversity, and phylogenetic analyses were performed using complete mitochondrial sequences, including and excluding non-coding regions.ResultsKey genetic variations were observed, including a non-canonical start codon (GTG) in the ND5 gene and an alternative stop codon (TAA) in ND4. Length polymorphisms in ND4L and cox1 suggested potential mitochondrial efficiency adaptations. Non-coding regions showed minor length differences, with the long non-coding region extending by 20 bp and the short by 4 bp. Sliding window analysis identified ND4 and ND5 as the most variable genes, while cox1, nd1,andcox2 were the most conserved. Phylogenetic analysis showed distinct clustering of Sudanese F. gigantica isolates with strong bootstrap support. Excluding the D-loop preserved phylogenetic structure, while D-loop-specific analysis revealed high variability, particularly in the sheep isolate.DiscussionThese findings highlight significant genetic variation and evolutionary divergence among F. gigantica isolates in Sudan. The observed diversity, particularly within non-coding and variable coding regions, underscores the influence of regional evolutionary pressures and host-associated adaptations. This work enhances understanding of F. gigantica’s genetic landscape and supports the development of more targeted molecular surveillance and control strategies for fascioliasis in endemic regions.